2007
DOI: 10.1152/ajpcell.00154.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fat accumulation with altered inflammation and regeneration in skeletal muscle of CCR2−/− mice following ischemic injury

Abstract: PK. Fat accumulation with altered inflammation and regeneration in skeletal muscle of CCR2Ϫ/Ϫ mice following ischemic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
148
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(167 citation statements)
references
References 66 publications
12
148
3
1
Order By: Relevance
“…In addition, monocytes do not express CXCR1 constitutively, which may explain the low levels of CXCR1 signal in the analysis. However, the kinetics of cell invasion is more similar to that of neutrophils in toxin-injected muscle (16,80,102), and monocytes are proliferative cells in inflamed tissues.…”
Section: Do M2 Macrophages Promote Muscle Regeneration?mentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, monocytes do not express CXCR1 constitutively, which may explain the low levels of CXCR1 signal in the analysis. However, the kinetics of cell invasion is more similar to that of neutrophils in toxin-injected muscle (16,80,102), and monocytes are proliferative cells in inflamed tissues.…”
Section: Do M2 Macrophages Promote Muscle Regeneration?mentioning
confidence: 91%
“…As in other tissues, Ly6Cϩ/F4/80-neutrophils are the first responders and begin to appear at elevated numbers within 2 h of muscle damage, typically peaking in concentration between 6 and 24 h postinjury and then rapidly declining in numbers. Following the onset of neutrophil invasion, phagocytic macrophages begin to invade, reaching significantly elevated concentrations at about 24 h postinjury and continue to increase in numbers until about 2 days postinjury, when their numbers begin to decline sharply (8,16,26,80,98,109,117). Their invasion precedes the elevation of a population of nonphagocytic macrophages that reaches peak concentrations in the muscle at about 4 days postinjury but remains significantly elevated for many days (Fig.…”
Section: Changes In Myeloid Cell Phenotype In Muscle Following Injurymentioning
confidence: 97%
See 1 more Smart Citation
“…Depending on the context, MPs may have supportive or deleterious eff ects on cells: in chronic diseases, including those aff ecting skeletal muscle, MPs are deleterious (62, 63), whereas they support tissue repair in muscle and other various tissues, including the liver, brain, peripheral nerve, and epithelium (19)(20)(21)(22)(64)(65)(66)(67). With the exception of regulation of infl ammation, studies documenting a direct role of MPs on cell behavior are scant and include intestinal progenitor proliferation (65), erythroblast proliferation and maturation (68), and oligodendrocytic diff erentiation and myelination (69).…”
Section: Articlementioning
confidence: 99%
“…Depletion of the macrophage population before cardiotoxin injection or after necrotic cell removal all lead to an impaired regeneration (6,7). Knock-out of chemokine CCL2 (Ϫ/Ϫ) or its receptor CCR2 (Ϫ/Ϫ) would result in impaired muscle regeneration with macrophages infiltration deficiency (8,9). We also previously reported that lack of chemokine CXCL16 leads to reduced macrophage infiltration, which causes poor muscle regeneration (10).…”
mentioning
confidence: 95%